PENGARUH PENAMBAHAN NATRIUM KLORIDA (NaCl) DAN WAKTU PERENDAMAN BUFFER FOSFAT TERHADAP PEROLEHAN CRUDE PAPAIN DARI DAUN PEPAYA (CARICA PAPAYA, L.) - Pinta Rizki Mala Hasibuan, Mitha Alviyulita, Farida Hanum (Universitas Sumatera Utara, 2014)
Papaya (Carica papaya L.) is one of the fruits of commodities internationally, either in the form of fresh fruit or as processed products. The leaves are green still not fully utilized. Papaya leaves contains papain enzyme which is a protease enzyme that very helpful for the industry. Papain is a protease enzyme contained in papaya latex, whether in fruit, stems and leaves, as an enzyme capable of solving the protein molecules, current papain into products that are beneficial to human life, either at home or industrial ladder. This study aims to determine the effect of the degree of saturation of sodium chloride and phosphate buffer to yield soaking rough papaya protease. This study varying the time of immersion phosphate buffer and saturation levels of sodium chloride. Analysis of protease activity was performed using UV-Vis spectrophotometer to measure the wavelength and absorbance values​​. The best research results obtained at 12 h immersion phosphate buffer with a concentration of sodium chloride 60% is 272.8222 unit / ml. In the analysis of the rendemen obtained by the best condition at the time of immersion phosphate buffer for 36 hours at a concentration of 90% is 43,5152%. In the analysis of moisture content obtained the best condition at the time of immersion of 36 hours at a concentration of 90% is 37.4266%.